56-6x=3x+21

Simple and best practice solution for 56-6x=3x+21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 56-6x=3x+21 equation:


Simplifying
56 + -6x = 3x + 21

Reorder the terms:
56 + -6x = 21 + 3x

Solving
56 + -6x = 21 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
56 + -6x + -3x = 21 + 3x + -3x

Combine like terms: -6x + -3x = -9x
56 + -9x = 21 + 3x + -3x

Combine like terms: 3x + -3x = 0
56 + -9x = 21 + 0
56 + -9x = 21

Add '-56' to each side of the equation.
56 + -56 + -9x = 21 + -56

Combine like terms: 56 + -56 = 0
0 + -9x = 21 + -56
-9x = 21 + -56

Combine like terms: 21 + -56 = -35
-9x = -35

Divide each side by '-9'.
x = 3.888888889

Simplifying
x = 3.888888889

See similar equations:

| 5-7x=3x+21 | | -70-9x=43-21x | | (5y-2)=52 | | 14-8x+6-5x=10+2x-5 | | 6x+18=116-6x | | (x+2)(2-x)=6x-x | | 2x+36=21x-36 | | 17-6x=4x-8 | | 9-5k+2k=k-23 | | x^2+4x-1=9x-5 | | 6x+30=13-33 | | x^2+8x-2=7 | | x^2-(a+2b)x+b^2+ab=0 | | 24a=36 | | 12-x=30-4x | | 3x+4=5x-16 | | x^2+32x-196=0 | | x-17=6x+8 | | 9x-5=x+19 | | 9x+6=6x+10 | | 7x-20=04-3x | | 7(2x-5)=42 | | 21-7x=10+4x | | x+2=-3x+30 | | (5x-3)*2+(2x+1)*2=34 | | .4x=-5.3 | | 2x+12=4x+2 | | 10-8=30-15x | | 5x+4y+5z-2x+2z-6y= | | 6x+36=8x+20 | | (x+1)*(2x-6)=0 | | 285-4x=41x+20 |

Equations solver categories